Financial distress, outside directors and corporate tax aggressiveness spanning the global financial crisis: An empirical analysis - Richardson, Grant; Lanis, Roman; Taylor, Grantley (Journal of Banking & Finance, 2015)
We examine financial distress and tax aggressiveness spanning the global financial crisis (GFC) of 2008 and the impact of the interaction between board independence and firm-specific financial distress on tax aggressiveness. Our regression results show that both financial distress and the GFC are positively associated with tax aggressiveness. More importantly, we find that the positive association between financial distress and tax aggressiveness is magnified by the GFC. We also observe that the interaction between board independence and financial distress is positively associated with tax aggressiveness. Our results are robust to multiple measures of financial distress and tax aggressiveness.